The Effect of Critical Thinking Ability and Learning Motivation on IPAS Learning Outcomes - Arum Maulidiyah; Rafia; Haeruddin; Mohammad Jamhari (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effect of critical thinking skills and student learning motivation on the learning outcomes of IPAS. The research was conducted at SD Negeri 2 Petobo using a survey method with a quantitative approach. Data collection involved administering critical thinking skills test questions and distributing learning motivation questionnaires, while IPAS learning outcomes were obtained from the mid-term test results of fifth-grade students. The sample consisted of 19 students, including 13 male and 6 female students. The collected data were analyzed using multiple regression analysis with SPSS. The normality test results confirmed that the data met the assumptions required for further statistical testing. The findings indicate that critical thinking skills and learning motivation significantly influence IPAS learning outcomes, as evidenced by an F-count value of 184.417 and an R-value of 0.967. Additionally, critical thinking skills were found to have a significant impact on student achievement in IPAS. Similarly, learning motivation was identified as a crucial factor affecting learning outcomes. These findings highlight the importance of fostering critical thinking and motivation to enhance students' academic performance. This study underscores the need for educators to integrate strategies that strengthen these aspects of the learning process.